2022
DOI: 10.1001/jamanetworkopen.2022.42742
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Anterior Cruciate Ligament Reconstruction in Patients With Anterior Cruciate Ligament Tear

Abstract: ImportanceThe timing of surgery has been regarded as a key factor in anterior cruciate ligament reconstruction (ACLR), and early vs delayed ACLR remains a controversial topic.ObjectiveTo synthesize up-to-date published data from randomized clinical trials (RCTs) comparing early vs elective delayed ACLR for patients with ACL deficiency, in terms of clinical outcomes and complications.Data SourcesThe PubMed, Cochrane Library, and Web of Science databases were systematically searched until September 9, 2022.Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In contrast, a Meta-analysis performed by Shen et al . revealed better IKDC and Lysholm scores in patients who underwent early ACLR (within 10 wk) compared to those who underwent late ACLR (within four months) 17. Also, the meta-analysis by Kay et al .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, a Meta-analysis performed by Shen et al . revealed better IKDC and Lysholm scores in patients who underwent early ACLR (within 10 wk) compared to those who underwent late ACLR (within four months) 17. Also, the meta-analysis by Kay et al .…”
Section: Discussionmentioning
confidence: 95%
“…16 In contrast, a Meta-analysis performed by Shen et al revealed better IKDC and Lysholm scores in patients who underwent early ACLR (within 10 wk) compared to those who underwent late ACLR (within four months). 17 Also, the metaanalysis by Kay et al demonstrated a significantly lower risk of concomitant meniscal injury, and chondral damage in patients who underwent an early ACLR (within six weeks) compared to those who underwent a late ACLR (up to 52 wk after the injury). 18 Almost the same results were reported in the metaanalysis performed by Kim et al, plus superior clinical function in the early ACLR group.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Shen et al evaluated 11 randomised controlled trials, including 972 patients in total, using the definition of early ACL reconstruction within 10 weeks. They found that early reconstruction was not associated with improved functional outcomes, nor with fewer complications [ 33 ]. Different time periods were defined by Evans et al, with early reconstructions within 3 weeks, and delayed reconstructions after 6 weeks [ 34 ], stating that there is still debate regarding the optimal timing.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of the relevance of the time span between injury and reconstruction is, generally in accordance with the most recent evidence. Here, the authors conclude, that “early ACLR was superior to elective delayed ACLR in terms of the Lysholm score at 2 years and the IKDC score” [ 37 ]. In contrast, it is also important to notice that most of the clinical outcomes were not different between early and late reconstruction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the authors conclude, that “early ACLR was superior to elective delayed ACLR in terms of the Lysholm score at 2 years and the IKDC score” [ 37 ]. In contrast, it is also important to notice that most of the clinical outcomes were not different between early and late reconstruction [ 37 ]. As the measures between the ACL injury and reconstruction, like pre-operative rehabilitation affects function, they must be considered, likewise [ 38 ].…”
Section: Discussionmentioning
confidence: 99%